Morfologia, propagação e inibidores de germinação do maracujazeiro doce e análise de fitotoxidez do lodo de esgoto - Freitas, Allan Rocha de (2016)
The sweet passion fruit (Passiflora alata Curtis) is a herbaceous plant, in general climbing plants, which features subcoriaceous leaves, solitary flowers, axillary, fragrant and fruit with sucosa pulp sweet and pleasant taste. Traditionally, commercial o